Law on supervisory activities of the National Assembly - The National Assembly (2003)
This Law prescribes the supervisory activities of the National Assembly, the National Assembly Standing Committee, the Nationality Council, the Committees of the National Assembly, the Associations of National Assembly deputies and the National Assembly deputies